Correlation between clinical outcomes and spinopelvic parameters in patients with lumbar stenosis undergoing decompression surgery - Maria Adriano Duque Costa (2020)
Purpose The aim of this study is to determine if there is a relation between preoperative sagittal alignment, based on radiographic parameters, and clinical outcomes, after lumbar decompressive procedures, in patients with lumbar spinal stenosis (LSS). Methods This study enrolled patients with LSS who underwent lumbar decompressive procedures, between January 2016 and December 2017. Preoperative spinopelvic parameters were measured, and patients were divided in radiological groups according to the median of the following variables: relative lumbar lordosis (measured minus ideal lumbar lordosis), relative pelvic tilt (measured minus ideal pelvic tilt) and sagittal vertical axis (SVA). Clinical outcomes were compared between these groups and included the Core Outcome Measures Index (COMI), EuroQoL Five Dimension Questionnaire (EQ-5D) and Oswestry Disability Index (ODI) scores before and 1-year after surgery. Further correlation statistics between sagittal radiological measurements and the postoperative outcome scores were performed. Results The study included 104 patients. We did not find any clinically important difference in clinical outcomes between radiological groups. However, in correlation analyses we found a significant but weak statistical correlation between relative lumbar lordosis and both preoperative and postoperative ODI, as well as a significant statistical negative correlation between SVA and postoperative EQ-5D. Conclusion Preoperative spinopelvic parameters did not significantly correlate with clinical outcomes after decompression surgery for LSS on non-deformity patients. Patients had a comparable improvement after surgery, regardless of their preoperative sagittal alignment.